In-flight and collisional dissipation as a mechanism to suppress Fermi acceleration in a breathing Lorentz gas - Oliveira, Diego F. M.; Leonel, Edson Denis [UNESP] (American Institute of Physics (AIP), 2012)
Some dynamical properties for a time dependent Lorentz gas considering both the dissipative and non dissipative dynamics are studied. The model is described by using a four-dimensional nonlinear mapping. For the conservative dynamics, scaling laws are obtained for the behavior of the average velocity for an ensemble of non interacting particles and the unlimited energy growth is confirmed. For the dissipative case, four different kinds of damping forces are considered namely: (i) restitution coefficient which makes the particle experiences a loss of energy upon collisions; and in-flight dissipation given by (ii) F = -eta V-2; (iii) F = -eta V-mu with mu not equal 1 and mu not equal 2 and; (iv) F = -eta V, where eta is the dissipation parameter. Extensive numerical simulations were made and our results confirm that the unlimited energy growth, observed for the conservative dynamics, is suppressed for the dissipative case. The behaviour of the average velocity is described using scaling arguments and classes of universalities are defined. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3697392]